Interelasi Pembaharuan Pendidikan Islam: Solusi Konflik Dikotomi Sains Islam Modern dan Tradisional - Dwi Fitri Wiyono (Qolamuna : Jurnal Studi Islam, 2020)
Abstract This article discusses the renewal of Islamic education found its significance through interlation methods over the dichotomy of modern and traditional Islamic science paradigms with conflict solution approaches. The results of studies and research in this journal are the reconstruction of Islamic education through interlation methods of islamic education reform, among others: First, make a firm distinction between normative Islam and historical Islam; second reconstruction of traditional Islamic sciences, Third, systematic historical studies, on the development of Islamic disciplines. Until now, Muslim intellectuals have not created an ethic of the Qur'an and social, both systematically and methodologically. Key words: Interlation, Renewal of Islamic Education, Dichotomy of Modern and Traditional Islam